Preventive Orientation of Iraqi Dentists in Baghdad in 2016 - Fatin Abd Alsttar Aledhari; katayoun Sargeran; Mahdia Gholami; Ahmad Reza Shamshiri (Tehran University of Medical Sciences, 2017)
Objectives: The aim of the present study was to assess the preventive orientation of Iraqi dentists in terms of their "knowledge" and "attitude" towards caries prevention and to explore their "preventive practice". Materials and Methods: A cross-sectional study based on a self-administered questionnaire was conducted among 159 dentists who worked in Baghdad during the summer of 2016. The questionnaires obtained information on variables such as knowledge and attitude towards preventive dentistry, preventive practice and demographic variables and were distributed during the official working time. Logistic and multiple regressions served for statistical analyses. Results: From all the respondents, 71% were females and the response rate was 94% (n=150). The mean age was 40.75±9.88 years (range 27-65 years). After checking for completeness, 90 questionnaires remained for data analysis. The most positive attitude towards preventive dental care was related to the question: "whether preventive dentistry is essential for the community" (n=75, 83%). The highest knowledge was reported in response to three questions: "frequency vs. amount of sugar consumption", "effect of sealant on caries prevention of newly erupted molars" and "effect of dental problems on general health" (n=83, 92.2%). The regression analysis showed a significant association between attendance in the continuing educational courses and preventive practice (P=0.03). Conclusions: To improve preventive dental orientation of Iraqi dentists, dental schools should put more emphasis on the topics about preventive dentistry. This will consequently improve their practice and oral health of the community.